Pengaruh Pembelajaran Kewirausahaan Terhadap Minat dan Motivasi Berwirausaha Siswa Di Smk Negeri 1 Selong Tahun Pembelajaran 2016 - Huzain Jailani; Muh Fahrurrozi (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2017)
The  purpose  of  this  study  was  to  determine  the  effect  of  the  interest  in entrepreneurship learning  and  entrepreneurship motivation  of students in SMK 1 Selong  learning  year  2016.  The  research  method  used  is  quantitative  method, while  the  data  collection  techniques  used  in  this  study  was  a  questionnaire, documentation, and observation. Analysis of the data used is descriptive statistical analysis and tested with normality and homogeneity. To test the hypothesis using a  simple  linearity  regression.  The  results  of  the  study  on  the  first  hypothesis  is There  was  a  significant  effect  on  the  interest  in  entrepreneurship  entrepreneurial learning  SMK  1  Selong  namely  T_hitung  =  6,059  with  significant  value  0.000 0.05,  then  H_0  H_a  rejected  and  accepted.  Great  relationship  or  influence  the interpretation of (R) 0.587 with determination R ^ 2 0.344 or 34.4%. The second hypothesis is There was a significant effect on the motivation of entrepreneurship entrepreneurial  learning  SMK  1  Selong  namely  T_hitung  =  9.080  with  0.000 significance value 0.05, then H_0 H_a rejected and accepted. Great relationship or  influence  the  interpretation  of  (R)  0.735  with  determination  R  ^  2  0.451  or 45.1%.  The  third  hypothesis  is  There  was  a  significant  effect  on  the  interest  in entrepreneurial learning and entrepreneurship motivation SMKN 1 Selong namely T_hitung = 8.488 with 0.000 significance value 0.05, then H_0 H_a rejected and accepted.  Great  relationship  or  influence  the  interpretation  of  (R)  0.712  with determination  R  ^  2  0.507  or  50.7%.  It  can  be  said  that  entrepreneurial  learning has an important role in increasing interest and motivation entrepreneurship class XII students in SMK 1 Selong learning year in 2016.